2006
DOI: 10.1182/blood-2005-07-2670
|View full text |Cite
|
Sign up to set email alerts
|

Lack of α4 integrin expression in stem cells restricts competitive function and self-renewal activity

Abstract: Alpha4 integrin or VLA4 (CD49d/CD29) is a multitask molecule with wide expression within and outside the hematopoietic system. Because targeted ablation of ␣4 integrin leads to embryonic lethality, to study its effects on adult hematopoiesis, we used animals with conditional excision of ␣4 integrin (␣4 ⌬/⌬ ) in hematopoietic cells. In such animals, we previously documented weakened bone marrow retention of progenitor cells during homeostasis and impaired homing and short-term engraftment after transplantation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 53 publications
3
59
0
Order By: Relevance
“…Thus, determination of ␣4 integrin levels on HSCs compared with T cells should be the preferred analysis method, as shown in Figure 1D. In line with previous data about the importance of VLA4 for stem cell homing and engraftment derived from conditional deleted knockout mice systems 5,6 or antibody blocking experiments, 8 we show that the level of ␣4 integrin expression, but not ␣6 expression, on CD34 ϩ cells correlated significantly with PBSC engraftment, independent of the total number of CD34 ϩ cells and/or history of radiation therapy. Our finding may have clinical impact because anticipation of PBSC engraftment capacity from ␣4 Figure 1.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, determination of ␣4 integrin levels on HSCs compared with T cells should be the preferred analysis method, as shown in Figure 1D. In line with previous data about the importance of VLA4 for stem cell homing and engraftment derived from conditional deleted knockout mice systems 5,6 or antibody blocking experiments, 8 we show that the level of ␣4 integrin expression, but not ␣6 expression, on CD34 ϩ cells correlated significantly with PBSC engraftment, independent of the total number of CD34 ϩ cells and/or history of radiation therapy. Our finding may have clinical impact because anticipation of PBSC engraftment capacity from ␣4 Figure 1.…”
Section: Resultssupporting
confidence: 82%
“…␣4␤1/VLA4 (CD49d/CD29), counter-receptor for VCAM-1 and fibronectin, as well as ␣6␤1/ VLA6/laminin receptor (CD49f/CD29) are ubiquitously expressed in human and mouse hematopoietic stem and progenitor cells, and both play a role in homing and engraftment of hematopoietic stem cells (HSCs). [2][3][4][5][6] Recent evidence from murine transplantation models suggests that ␣4-chain deletion 5 or treatment with functionblocking antibodies to ␣4 or ␣6 integrin 4 may impair hematopoietic engraftment. In contrast, it is reported that blockage with ␣6 integrin antibodies improves engraftment efficiency in human HSCs.…”
mentioning
confidence: 99%
“…Conditional deletion of VLA-4 shows that this integrin is required for normal HSPC activity. 35 Similarly, genetic ablation of VCAM-1 leads to constitutive mobilization, that is enhanced with G-CSF. 36 Moreover, antibodies to VCAM-1 or VLA-4 mobilize HSPCs in both mice 37 and humans.…”
Section: G-csf Mobilizes Hspcs Through a Hematopoietic Intermediatementioning
confidence: 99%
“…28 Whether this integrin axis may compensate for the lack of CXCR4 signaling during colonization of fetal liver by HSC from CXCR4 À/À or SDF-1 À/À mice and guides engraftment of CXCR4 À/À fetal liver HSC cells after transplantation into normal littermates is not clear at this point. Alternatively, it is possible that engraftment of CXCR4 À/À HSC could be somehow compensated by the RDC1 receptor mentioned above, 16 or perhaps by a recently described homing mechanisms involving a calcium-sensing receptor.…”
Section: The Role Of the Sdf-1-cxcr4 Axis In Normal Development And Hmentioning
confidence: 99%